2000
DOI: 10.1046/j.1360-0443.2000.951217717.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based pharmacokinetic approach for methadone monitoring of opiate addicts: potential clinical utility

Abstract: Using plasma monitoring in combination with the application of Bayesian forecasting it should be possible to predict trough levels of methadone during daily dosing. The model is able to utilize sparse sampling, and two blood samples are expected to be sufficient to define patient compliance. Random samples during treatment could be used to assess methadone dosing by comparing predicted with observed measurements for each individual. The clinical tool could therefore help to detect incomplete (failure to consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…The slowed rate and attenuation of the development of tolerance may be beneficial in MMT long term (limited dosage escalation) and helpful in pain relief (enabling very high dosing) but contradictory during methadone induction or in methadone-naive individuals. Lack of tolerance and rapid escalation of dose has been highlighted as associative of overdose risk (55,60,124). Concomitant consumption of other NMDA antagonists with methadone, particularly ethanol (also a CNS depressant), can potentiate the effects of the opioid and increase the risk of overdose (126).…”
Section: Cellular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slowed rate and attenuation of the development of tolerance may be beneficial in MMT long term (limited dosage escalation) and helpful in pain relief (enabling very high dosing) but contradictory during methadone induction or in methadone-naive individuals. Lack of tolerance and rapid escalation of dose has been highlighted as associative of overdose risk (55,60,124). Concomitant consumption of other NMDA antagonists with methadone, particularly ethanol (also a CNS depressant), can potentiate the effects of the opioid and increase the risk of overdose (126).…”
Section: Cellular Mechanismsmentioning
confidence: 99%
“…Rate of loss of tolerance is dependent on the rate of elimination of the opioid, which for methadone is prolonged and variable (124)(125), but also on the rate at which functional opiate receptors become available again for activation. Risk of overdose is thus dependent upon the affinity or efficacy of methadone at receptor subtypes and current or previous opioid exposure.…”
Section: Molecular Considerations-tolerancementioning
confidence: 99%
“…Research studies on quality of life have also involved maintenance treatments involving opioids such as methadone and buprenorphine (Ajir et al, 1998;Caplehorn, 1994;Caplehorn et al, 1993;D'Aunno & Pollack, 2002;D'Aunno & Vaughn, 1992;Everhart et al, 1997;Ling & Wesson, 2003;Mendelson et al, 1995;Schuh & Johanson, 1999;Strain et al, 1999;Torrens, Domingo-Salvany, Alonso, Castillo, & San, 1999;Torrens et al, 1997;Schwartz, Brooner, Montoya, Currens, & Hayes, 1999;Wolff, Rostami-Hodjegan, Hay, & Tucker, 2000;Ventegodt & Merrick, 2003). 0740 Methadone maintenance treatment programs can offer an effective treatment for opioid addiction.…”
Section: Introductionmentioning
confidence: 97%
“…It has been suggested that these factors may explain about 33 percent of the inter-individual variations in Vss. These parameters are found to be higher in females and they are directly related to weight (Wolff et al, 2000). Furthermore, it has also been suggested that a time-dependent increase in methadone clearance may result from auto-induction of its own metabolism by CYP3A4, and the change in Vss may be due to up or down-regulation of AAG (Rostami-Hodjegan et al, 1999).…”
Section: Distributionmentioning
confidence: 98%